If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(t + -6) + 3t = 6(2t + 5) + -10 Reorder the terms: 9(-6 + t) + 3t = 6(2t + 5) + -10 (-6 * 9 + t * 9) + 3t = 6(2t + 5) + -10 (-54 + 9t) + 3t = 6(2t + 5) + -10 Combine like terms: 9t + 3t = 12t -54 + 12t = 6(2t + 5) + -10 Reorder the terms: -54 + 12t = 6(5 + 2t) + -10 -54 + 12t = (5 * 6 + 2t * 6) + -10 -54 + 12t = (30 + 12t) + -10 Reorder the terms: -54 + 12t = 30 + -10 + 12t Combine like terms: 30 + -10 = 20 -54 + 12t = 20 + 12t Add '-12t' to each side of the equation. -54 + 12t + -12t = 20 + 12t + -12t Combine like terms: 12t + -12t = 0 -54 + 0 = 20 + 12t + -12t -54 = 20 + 12t + -12t Combine like terms: 12t + -12t = 0 -54 = 20 + 0 -54 = 20 Solving -54 = 20 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x-10=-14 | | 6x-(3x-8)=16 | | 6(w+4)=3w+9 | | 3y-3=-6 | | 2w-8+w+8+2w+4=90 | | 5(x+2)=x+2 | | 13-4k=5 | | 4u^2+25u+31=0 | | 16y^2+16y+4=0 | | 9a^2=81 | | 6y+5=4y-7 | | 3-2(a+2+a)=5a+8 | | y^2+y-12=0 | | 12x^2+9=-6x | | 1x-4(x+3)=4-2x | | 9-18x+9x^2=0 | | 2u^2+9u-18=0 | | 3x^2+10xy+5y^2+20=0 | | y-(y+3)=y+y | | 5w^2+11w-2=0 | | 6p^2=-11p-40 | | 5(b-4)=10b+4 | | 5(b-4)=10y+4 | | 4v^2+8v+15=0 | | 8x+10=570 | | 2k^2-20=-k | | 4y+5=31 | | 4x^3+5x+1=0 | | 45x^2-120xy+80y^2=0 | | 6x^2-10x+10=0 | | 9x^3+39x^2+42x=0 | | 6y-2=5y+8 |